Mesoporous materials modified by aptamers and hydrophobic groups assist ultra-sensitive insulin detection in serum1. Issue 71 (14th September 2015) - Lei, Chang; Xu, Chun; Noonan, Owen; Meka, Anand Kumar; Zhang, Long; Nouwens, Amanda; Yu, Chengzhong
<x xml:space="preserve">Abstract</x> A mesoporous material modified with insulin-binding-aptamers and –CH3 is applied in sample pre-treatment to enhance the limit-of-detection of ELISA 30-fold.